Analysis of Service System using Simulation - Al-Zaher, Abdulqader; Indiyanto, Rus; Donoriyanto, Dwi Sukma (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
Simulation is a method for evaluating model behavior in various situations that allow decision making. This simulation requires the development of a model that represents the system. Therefore, the simulation will act as a system operation. After carrying out model simulations, the real impact of each alternative and action will be identified. Discrete simulation models the operation of a system as a series of discrete events in time. Each event occurs at a specific time and marks a change in state in the system. Due to changes in the system, this simulation will prevent failures without disrupting the actual system. The results of verification and validation obtained 3 replications with an average replication time in real time, namely 19.33 minutes and in ProModel software, namely 9.65 minutes. Based on the confidence interval, the output results obtained in the ProModel simulation are with the interval [5.888 ≤ μ1 – μ2 ≤ 13.478], because the value 0 is not within the range μ1 – μ2 so it can be said that the data obtained is invalid. This means that there is a difference between the time in the real system and the simulation output results with the Promodel software. Because the results obtained are not yet valid, the simulation output cannot be applied to real service system processes at Coffee X. Suggestions for further research are to be more careful in inputting data and re-checking it, so that the simulation output obtained will be valid so that it can be applied to real situations.